Novel Adiponectin Receptor Agonist Inhibits Cholangiocarcinoma via Adenosine Monophosphate-activated Protein Kinase - Bui, Khac C.; Nguyen, Thi M. L.; Barat, Samarpita; Scholta, Tim; Xing, Jun; Bhuria, Vikas; Sipos, Bence; Wilkens, Ludwig; Nguyen, Linh Toan; Le, Huu Song; Velavan, Thirumalaisamy P.; Bozko, Przemyslaw; et al. (Current Medicinal Chemistry, 2024)
Background: Cholangiocarcinoma (CCA) has a poor prognosis and only limited palliative treatment options. The deficiency of adiponectin and adenosine monophosphate-activated protein kinase (AMPK) signaling was reported in several malignancies, but the alteration of these proteins in CCA is still unclear. Objectives: This study aimed to assess the role of adiponectin and AMPK signaling in CCA. Furthermore, AdipoRon, a novel adiponectin receptor (AdipoR) agonist, was evaluated in vitro and in vivo as a new anti-tumor therapy for CCA. Methods: The expression of AdipoR1 and p-AMPKα in human tissue microarrays (TMAs) was evaluated by immunohistochemistry staining (IHC). The effect of 2-(4-Benzoylphenoxy)-N-[1-(phenylmethyl)-4-piperidinyl]-acetamide (AdipoRon) was investigated in vitro with proliferation, crystal violet, migration, invasion, colony formation, senescence, cell cycle and apoptosis assays and in vivo using a CCA engineered mouse model (AlbCre/LSL-KRASG12D/p53L/L). RT-qPCR and western blot methods were applied to study molecular alterations in murine tissues. Results: AdipoR1 and p-AMPKα were impaired in human CCA tissues, compared to adjacent non-tumor tissue. There was a positive correlation between the AdipoR1 and p-AMPKα levels in CCA tissues. Treatment with AdipoRon inhibited proliferation, migration, invasion and colony formation and induced apoptosis in a time- and dose-dependent manner in vitro (p<0.05). In addition, AdipoRon reduced the number of CCA and tumor volume, prolonged survival, and decreased metastasis and ascites in the treated group compared to the control group (p<0.05). Conclusions: AdipoR1 and p-AMPKα are impaired in CCA tissues, and AdipoRon effectively inhibits CCA in vitro and in vivo. Thus, AdipoRon may be considered as a potential anti-tumor therapy in CCA.
Keywords: therapy